EFFECTIVE DETERRENCE: WHEN IS DETERRENCE THE “RIGHT” STRATEGY FOR ACHIEVING NATIONAL INTERESTS? - Kopanja, Mihajlo (Serbian political thought, 2023)
The research goal of this paper is to determine the circumstances in which the strategy of deterrence is the "right thing" for the security of the state. In the pursuit of realizing their own interests – from minimum survival to maximum hegemony, states (in theory) have a wide range of possible ideal-type strategies. However, this does not mean that all possible strategies will be equally effective for achieving national interests. This paper strives to determine which conditions should be met in order for the implementation of deterrence to be the most effective strategy, that is, the "right thing" for the security of the state. For this purpose, the work is organized in three parts. In the first unit, the concept of strategic effectiveness is elaborated. In the second part, the author provides a brief overview of deterrence as a strategy, presenting the key theoretical-conceptual elements of this strategy. The third part of the paper presents the conditions that must be met in order for the deterrence strategy to be effective, i.e. the "right thing" for realizing national interests. Finally, in the final segment of the paper, the author looks at the case of the Republic of Serbia, considering whether deterrence is an effective solution in modern circumstances.